Experimental and computational evidence for a stabilising C–Cl(lone-pair)⋯π(chelate-ring) interaction - Tan, Sang Loon *; Lee, See Mun *; Lo, Kong Mun *; Otero-de-la-Roza, Alberto; Tiekink, Edward R. T. * (Royal Society of Chemistry, 2021)
In addition to a variety of conventional non-covalent intermolecular interactions such as C–H…π(arene), C–H…Cl and π(arene)…π(chelate-ring) contacts, the molecular packing in the crystal of an organotin dithiocarbamate compound, [SnCl(4-ClC6H4)2{S2CN(i-Pr)2}], exhibits evidence for a C–Cl…π(chelate-ring) interaction. These interactions occur via a side-on approach of the chloride atom to the chelate-ring and therefore, are characterised as C–Cl(lone pair)…π(chelate-ring) interactions, are shown to be attractive by NCI plots and QTAIM analysis, and are apparent in the calculated Hirshfeld surfaces. Theory suggests the energy of association provided the C–Cl…π(chelate-ring) interactions to be about 3-4 kcal/mol, a value greater than for analogous C–Cl…π(arene) and C–H…π(arene) interactions. A survey of the literature of related structures suggests these interactions are not common. The newly described C–Cl(lone-pair)…π(chelate-ring) interactions add to the variety of intermolecular interactions able to be formed by chelate-rings in the supramolecular chemistry of metal complexes.